Diversity and composition of fish fauna at Telaga Air Estuary - Faznur Fateh, Bte Firdaus@Nicholas (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study was conducted to determine the diversity and composition of fish fauna at Telaga Air estuary from 4th _5 th February 2012. Five sampling stations were selected and fish were collected using three layer gill net after the 10 to 15 minutes of net deployment. A total of 237 individual fish from 26 families and 52 species were collected. The highest individual fish were collected at ST3 and the lowest at ST5. The most ubiquitous fish collected were from family Sciaenidae with 10 species and covered 32.70% of individual fish. Eight types of physico-chemical water parameters were taken and analyze using one way ANOV A showed that there were significant differences among all stations.